Visionary Leadership in a Turbulent World Thriving in the New VUCA Context - Elkington, Rob (Emerald Publishing Limited, 2017)
Visionary Leadership in a Turbulent World: Thriving in the New VUCA Context, is the thoughtful analysis of nine expert authors from around the globe who put VUCA under the microscope and take the reader on a journey that looks at VUCA from a number of different leadership perspectives